The Genesis of Greek Philosophico-Scientific Thought in Islamic and Modern Historiographies of Science: A Brief Comparative Overview - Setia, Adi (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Genesis of Greek Philosophico-Scientific Thought in Islamic and Modern Historiographies of Science: A Brief Comparative Overview